2016
DOI: 10.1002/ange.201601238
|View full text |Cite
|
Sign up to set email alerts
|

White Graphene undergoes Peroxidase Degradation

Abstract: Hexagonal boron nitride (hBN) nanosheets are emerging as promising 2D materials for different types of applications. However, biodegradation of hBN materials is poorly explored owing to their high chemical inertness and strong oxidation resistance. The assessment of oxidation/biodegradation of hBN is important in developing biomedical tools. Herein, we report the first study on the biodegradability of hBN nanosheets comparing the enzymatic catalysis of two different peroxidases, horseradish peroxidase (HRP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…On the other hand, by incubating LM nanocapsules with a common enzyme, HRP and H 2 O 2 under static conditions, these LM nanocapsules were effectively oxidized. Indeed, the transmittance of LM nanocapsules was rapidly increased and formed precipitations at the bottom of a vial after treatment with a combination of HRP and H 2 O 2 for only 1 h. The formation of a highly oxidizing intermediate from this enzyme, known as Compound I, facilitates this biodegradation process454647. The obtained data clearly indicate that ROS has capability to destruct the polymer shells on LMs although it takes time to completely decompose them because of strong crosslinked shell structures.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, by incubating LM nanocapsules with a common enzyme, HRP and H 2 O 2 under static conditions, these LM nanocapsules were effectively oxidized. Indeed, the transmittance of LM nanocapsules was rapidly increased and formed precipitations at the bottom of a vial after treatment with a combination of HRP and H 2 O 2 for only 1 h. The formation of a highly oxidizing intermediate from this enzyme, known as Compound I, facilitates this biodegradation process454647. The obtained data clearly indicate that ROS has capability to destruct the polymer shells on LMs although it takes time to completely decompose them because of strong crosslinked shell structures.…”
Section: Resultsmentioning
confidence: 84%
“…The processes used for H 2 O 2 - and HRP oxidation-based degradations of LM nanocapsules were similar ways to those described previously for nanocarbons454647. The LM nanocapsules were dispersed in water at a concentration of ∼1 mg ml −1 ; this dispersion (0.3 ml) was mixed with PBS (0.7 ml) containing H 2 O 2 (10 μl of 80 mM).…”
Section: Methodsmentioning
confidence: 99%
“…Although carbon nanomaterials have been postulated as being structurally persistent, various studies have recently demonstrated that peroxidases are able to catalyze the oxidative degradation of some nanostructures . On the other hand, though a few articles have investigated both biodistribution and tumor targeting ability, the nanocarrier biodegradation capacity has not been thoroughly investigated.…”
Section: Resultsmentioning
confidence: 99%
“…36 The available literature suggests that degradation of the GFMs and other 2D materials is possible in vivo by the action of immune cells like neutrophils and macrophages. Until now, degradation of carbon nanomaterials and 2D materials, including hexagonal boron nitride (hBN), 5,37 MoS2, 7,34,35,38,39 WS2, 40 MnO2, 41 black phosphorous, 42,43 has been reported. In addition, there are many other 2D materials like MXenes, graphitic C3N4, 2D clay materials, and others showing potential biomedical and environmental applications.…”
Section: Current Views and Future Directionsmentioning
confidence: 99%
“…We reported, for instance, that HRP does not degrade hBN up to 60 days, while MPO partially degrades hBN within 35 h. An almost complete degradation of hBN leading to soluble boron oxide species occurred by photo-Fenton reaction in 100 h. In addition, high-dispersible hBN was more degradable compared to the aggregated sheets. 5,37 We also examined the biodegradability of water dispersible pristine and functionalized MoS2 nanosheets. 7 Exfoliated MoS2 sheets resulted more degradable than the functionalized materials by MPO.…”
Section: Current Views and Future Directionsmentioning
confidence: 99%